Comparative Evaluation of HFC‐134a Decompositions Over Metal‐Impregnated γ‐Al2O3 Catalysts (M/γ‐Al2O3) (M = Mg, Ni, Co, Zn, Cu) - Myeong‐Heon Yoo; Hyeonsuk Yoo; Yongjin Lee; Seok‐Goo Lee; Seung‐Hyun Moon; Tae‐Sung Jung; Churl‐Hee Cho; Heon‐Do Jeong; Dong‐Woo Cho (Advanced Energy & Sustainability Research)
Al2O3, widely used in the catalytic decomposition of fluorocarbons, is known to be rapidly deactivated owing to its transformation to AlF3. Accordingly, in this study, metal‐impregnated γ‐Al2O3 catalysts (M/γ‐Al2O3) were synthesized and their long‐term stabilities for HFC‐134a decomposition were investigated under the conditions of 10,000 ppm HFC‐134a in air balance. Although γ‐Al2O3 and Mg/γ‐Al2O3 demonstrated long‐term activities, significantly longer than those of the other catalysts, activity of γ‐Al2O3 rapidly decreased, whereas that of Mg/γ‐Al2O3 gradually decreased. Although Mg/γ‐Al2O3 exhibited the smallest Brunauer‐Emmett‐Teller specific surface area among those of the synthesized catalysts, it demonstrated excellent long‐term stability and the lowest deactivation rate due to the high total amount of weak acid sites. Mg/γ‐Al2O3 exhibited considerably smaller crystal size of AlF3 compared to other catalysts. Additionally, after HFC‐134a decomposition, the morphology of Mg/γ‐Al2O3 was clearly less modified and metal agglomeration was lower than those of other catalysts. Finally, this was caused by the reaction of Mg with HF, forming MgF2, which inhibited the complete conversion of γ‐Al2O3 to AlF3 and produced AlOFX, an intermediate compound. These results suggest that Mg impregnation in γ‐Al2O3‐based catalysts is a suitable method for enhancing the performances of these catalysts in the long‐term decomposition of HFC‐134a.